2006
DOI: 10.1021/jo060594+
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Heterocyclic Carbene Precursors

Abstract: A series of N-heterocyclic carbene precursors, containing an imidazoline or tetrahydropyrimidine framework, were prepared from omega-chloroalkanoyl chlorides. The sequential attachment of nitrogen nucleophiles and subsequent ring closure gave, depending on the reagents used, either the desired dihydroimidazolium and tetrahydropyrimidinium salts or their parent heterocycles. In this latter case, the second substituent was introduced in an alkylation step. The preparation of carbene precursors bearing chiral or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 46 publications
2
34
0
1
Order By: Relevance
“…Recently, the use of CO 2 adducts of NHCs attracted much attention in organocatalysis as well as in synthesis of the corresponding NHC-metal complexes. [6,7,28] In this article, we describe the synthesis and application of a polymer-supported, CO 2 -protected N-heterocyclic carbene. It was prepared via ring-opening metathesis copolymerization of 1,4,4a,5,8,8a-hexahydro-1,4,5,8-…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of CO 2 adducts of NHCs attracted much attention in organocatalysis as well as in synthesis of the corresponding NHC-metal complexes. [6,7,28] In this article, we describe the synthesis and application of a polymer-supported, CO 2 -protected N-heterocyclic carbene. It was prepared via ring-opening metathesis copolymerization of 1,4,4a,5,8,8a-hexahydro-1,4,5,8-…”
Section: Introductionmentioning
confidence: 99%
“…[14] A number of synthetic routes to substituted imidazolinium proligands have been developed. These include a modular substituted diamine synthesis with subsequent ring closure, [15] multicomponent synthesis by using a combination of amine, aldehyde, isocyanide and alkyl halide, [16] the intramolecular "hydroamidiniumation" of alkenes, [17] and a template synthesis with an azido isocyanide at a tungsten metal centre. [18] Late metal complexes containing alcohol and phenolfunctionalised saturated NHC ligands have been reported, see Figure 2: Seeking an analogy with salicylaldimine ligands, Grubbs reported the synthesis of o-hydroxyaryl-substituted NHCs and showed that the Pd adducts C were stable.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ramírez et al reported the synthesis of two derivatives, by a three-step strategy starting from ω−haloalkanoyl chlorides, 21 in which the substituted amino group is generated from an amide, while the primary amine results from reduction of an azide. 22 N-Alkylation is conceptually the most straightforward disconnection towards secondary and tertiary amines. 23 Although this transformation seems rather simple, the fact that the newly formed amines are also nucleophilic brings about the formation of bisand/or polyalkylation by-products.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%